The scaling relationship between degree centrality and citation-based impact of articles on strategic management - Ronda-Pupo, Guillermo Armando (2019)
The aim of this study is to explore the scaling relationship between degree centrality and citation-based performance of countries articles on Strategic Management. The results show a scaling relationship between Impact and degree centrality with scaling exponent of 1,28 ± 0,07. This result suggests that the Impact of a countries’ articles on strategic management increases non-linearly with degree centrality 21,28 o 2,42 times when the country doubles its degree centrality. The results suggest that the increase of the participation of countries in international collaborative networks on strategic management research is a positive strategy to foster the international visibility and impact on strategic management research.